2020
DOI: 10.1016/j.bbrc.2020.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Single cell RNA sequencing of 13 human tissues identify cell types and receptors of human coronaviruses

Abstract: a b s t r a c tThe new coronavirus (SARS-CoV-2) outbreak from December 2019 in Wuhan, Hubei, China, has been declared a global public health emergency. Angiotensin I converting enzyme 2 (ACE2), is the host receptor by SARS-CoV-2 to infect human cells. Although ACE2 is reported to be expressed in lung, liver, stomach, ileum, kidney and colon, its expressing levels are rather low, especially in the lung. SARS-CoV-2 may use co-receptors/auxiliary proteins as ACE2 partner to facilitate the virus entry. To identify… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
800
1
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 838 publications
(867 citation statements)
references
References 36 publications
43
800
1
23
Order By: Relevance
“…7E). Consistently with previously report 31 , ACE2 was mainly expressed in alveolar type 2 cells in lung ( Fig. 7D-E).…”
Section: Higher Expression Of Furin Than Ace2 In Different Organs Atsupporting
confidence: 93%
See 1 more Smart Citation
“…7E). Consistently with previously report 31 , ACE2 was mainly expressed in alveolar type 2 cells in lung ( Fig. 7D-E).…”
Section: Higher Expression Of Furin Than Ace2 In Different Organs Atsupporting
confidence: 93%
“…Among ZJ01 unique mutations, 10 (NO. [22][23][24][25][26][27][28][29][30][31] were located on the S protein, including 3 samesense mutation, 2 deletion mutation and 5 missense mutation, which led to amino acid changes of Ser596, Gln613, Glu702, Ala771, Ala1015, Pro1053 and Thr1066. Further similarity analysis indicated that the main difference among various coronaviruses located in the Receptor Binding Domain (RBD) region of S1.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…S4A-E). This is very different to the small intestine where ACE-2 appears to be more expressed (Qi et al, 2020). This low ACE-2 level could explain why we have a small percentage of infected cells in our colon organoids (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Specifically, nasal goblet cells and multiciliated cells comprised the highest fraction of dualpositive ACE2 + TMPRSS2 + cells 45 , consistent with a plausible role for a nasal viral reservoir that supports transmissivity. In the distal lung, co-expression occurred in AT2 cells 45,47,48 . Previous surveys across other tissues also showed a relatively high portion of ACE2 + TMPRSS2 + cells within colonic enterocytes, another potential viral reservoir that promotes viral transmission 49 .…”
Section: A Cross-tissue Survey Identifies Dual-positive Ace2 + Tmprssmentioning
confidence: 97%